IMPACT OF THE COVID-19 PANDEMIC ON ESTIMATING ELECTRICITY DEMAND AND SUPPLY IN LAMPUNG PROVINCE USING A SIMPLE LINEAR REGRESSION AND CORRELATION APPROACH - Ilmi, Aulia Nurul; Brajamusti, Jati Kinsela; Hasan, Muhammad Rafid; Pratama, Daniel Putra; Akraam, Ajie Alvido (Indonesian Journal of Electrical Engineering and Electronics, 2023)
This research was conducted to predict the effect of COVID-19 to the total of energy produced by the amount of electricity per capita. The amount of energy produced has the property of being an independent variable or can be affected and electricity consumption per capita has the nature of being an independent or influential variable. This research examines the effect of per capita electricity consumption on the total amount of energy produced in the Lampung region. The research was conducted using regression and correlation experiments. Regression research proves that there is no relationship between electricity consumption per capita and the total amount of energy produced. In contrast, in the linear correlation experiment, there is a correlation between electricity consumption per capita and the total amount of energy produced.